Adverse outcome pathways as a new approach to assess toxicity in drug development - Antonijević Miljaković, Evica; Djukić-Ćosić, Danijela; Ćurčić, Marijana; Buha Djordjević, Aleksandra; Bulat, Zorica; Baralić, Katarina; Javorac, Dragana; Marić, Djurdjica; Antonijević, Biljana (Archives of Pharmacy, 2022)
Adverse outcome pathways (AOPs) represent tool in toxicology, introduced in 2010 by scientists from the US Environmental Protection Agency as framework to support ecotoxicological research and risk assessment. In 2012 Organization for Economic Cooperation and Development initiated an international AOPs development program. Since then, AOPs have been promoted as useful tools in health risk assessment, development of Integrated Approaches to Testing and Assessment and for developing novel animal-free test methods. AOPs provide structured frameworks for collecting, organizing and evaluating existing toxicological knowledge on mechanistic pathways. AOPs describe biologically plausible chains of events linking a molecular initiating event to key events at different levels of biological organization and finally to an adverse outcome. Not being stressor-specific, the ultimate utility of AOPs should be to predict adverse effects of any type of stressor, including chemicals, nanomaterials, pharmaceuticals etc. with unknown toxic effects but for which the toxicological mechanisms are known or can be tested. AOPs have been suggested as structured basis for predicting drug-induced liver injury (steatosis, fibrosis, cholestasis) and for developing in silico and in vitro methods for screening as well as targeted methods for pre-clinical testing to assess liver toxicity, being the common reason for withdrawing pharmaceuticals from the market. AOPs have also been proposed as useful frameworks for method development and integration of in vitro data in personalized cancer therapy. In conclusion, AOPs concept plays an important role in 21st century toxicology paradigm supporting predictive toxicology with alternative assays and reduction of the need for animal use.